THE UTILIZATION OF THE KINDS OF LIVE FOOD ON CLOWN LOACH FISH JUVENILES (Chromobotia macracanthus Bleeker) - Nina Meilisza; Rina Hirnawati; Sulasy Rohmy; Agus Priyadi; Jacques Slembrouck (Indonesian Aquaculture Journal, 2011)
Domestication and mass production technology of clown loaches fish have been developed by the Research Institute for Ornamental Fish Culture, Depok and the Institute de Recherche pour le Developpement (IRD). In the process, some constraints has been found and one of them was the cost of production and sustainable supply of Artemia as the only one of live food which used for clown loaches post-larvae until 2-3 months old juvenile. To solve this constraints, the use of other live feed as a substitute or replacement of Artemia should be applied, caused by it research of the utilization of the kinds of live food on clown loach juvenile need to be done. This research aims to determine the kinds of live food which be recommended for the substitution of Artemia on clown loaches fish juvenile (Chromobotia macracanthus Bleeker). Research carried out using 1 month old clown loach juveniles designed into the Complete Randomized Design in two factors namely are class of fish size S (35-50 mg), M (55-70 mg), L (75-90 mg) and the kinds of live food in the form of Artemia as a control, Moina, mini maggot, blood worms (Chironomus), and silk worms (Tubifex). Three levels treatment by class of fish size factor and five levels treatment by the kinds of live food factor produce 15 kinds of interactions with duplications. The research was conducted at recirculation system for 8 weeks to 3 months old juveniles. Observations were carried and measuring the growth parameters including weight, total length of fish, as well as survival rate parameters based on the number of fish that live at the end of the research. The support is done by measuring the water quality of pH, DO, temperature, ammonia, conductivity, and nitrites, proximate analysis of feed also performed. The two of research step analyzed by ANOVA (Analysis of Variance) and continued by Tukey test.